Contribution of vegetation and peat fires to particulate air pollution in Southeast Asia - C L Reddington; M Yoshioka; R Balasubramanian; D Ridley; Y Y Toh; S R Arnold; D V Spracklen (Environmental Research Letters, 2014)
Smoke haze, caused by vegetation and peat fires in Southeast Asia, is of major concern because of its adverse impact on regional air quality. We apply two different methods (a chemical transport model and a Lagrangian atmospheric transport model) to identify the locations of fires contributing to the increased mass concentration of particulate matter with diameters less than 2.5 μ m (PM _2.5 ) in Singapore over the period 2004–09. We find that fires in southern Sumatra account for the greatest percentage of the total fire enhancement to PM _2.5 concentrations in Singapore (42–62%), with fires in central Sumatra and Kalimantan contributing 21–35% and 14–15%, respectively. Furthermore, we find that fires in these regions also increase PM _2.5 concentrations in other major cities across Southeast Asia. Our results suggest that acting to reduce fires in southern and central Sumatra (specifically in the eastern parts of the provinces of Jambi, South Sumatra, Lampung and Riau) and southwest Kalimantan (the southern extent of the provinces of West, Central and South Kalimantan) would have the greatest benefit to particulate air quality in Singapore and more widely across Southeast Asia.